Health specialists' views on the needs for developing a digital gaming solution for paediatric day surgery: A qualitative study. Issue 17 (9th July 2020) - Rantala, Arja; Pikkarainen, Minna; Pölkki, Tarja
Abstract: Aims and objectives: To describe the views on the needs of health specialists to consider when developing a digital gaming solution for children and families in a paediatric day surgery. Background: Children's day surgery treatment is often cancelled at the last minute for various reasons, for example due to the lack of information. Digital gaming solutions could help families to be better oriented to the coming treatment. Despite the increasing demands for mHealth systems, there is not enough evidence‐based information from the health specialist perspective for developing a digital gaming solution. Design: A qualitative descriptive study was conducted. Methods: Health specialists ( N  = 15) including 11 nurses, one physiotherapist and four doctors from different areas from one university hospital in Finland were recruited using a snowball sampling method. Semi‐structured, face‐to‐face interviews were conducted in March and April 2019. The data were analysed using inductive conduct analyses. The COREQ checklist was used to report the data collection, analysis and the results. Results: The data yielded 469 open codes, 21 sub‐categories, three upper categories and one main category. The main category the digital gaming solution to support knowledge, care and guidance in children's day surgery included three upper categories: (a) support for preoperative information and guidance, (b) support for intra‐operative information and care, and (c) support for postoperative information, care and guidance. Conclusion: Digital gaming solutions could be used to help children and families to be better prepared for upcoming treatments, to support communication in different languages and to improve children's pain management after operations. Relevance to clinical practice: Evidence‐based information is important to ensure that future digital solutions answer the real needs of the staff and patients. There is a need for families and children's views to be taken into consideration when developing digital gaming solutions in the hospital context.